PENGARUH ANTARA LABA AKUNTANSI DAN TOTAL ARUS KAS TERHADAP HARGA SAHAM: STUDI PADA PERUSAHAAN SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Fitri, Raisa (LP2M Institut Teknologi dan Bisnis Asia Malang, 2016)
This strong growth is happening because of the expansion of the Indonesian economy is fertile. Consumer spending makes a strong middle class residential business segment was the largest contributor to growth in Indonesia properties .. In this study, the parameters used to measure the performance of the company's financial statements is the accounting profit and the total cash flow. This study aims to examine and analyze the effect of variable accounting profit, and total cash flow to share price. Using multiple regression analysis, the study population is all companies sub-sector property and real estate listed on the Indonesia Stock Exchange in 2013-2015. The results showed that the accounting profit that affect stock prices. Accounting profits will provide information and a positive signal on the stock price on the property sub-sector and real estate, so it will affect the reduction or increase in the company's stock price. Total variable cash flows do not affect the stock price. Data in the cash flow statement only provide weak support for investors.